Islam Nusantara : Pribumisasi Islam ala NU - Ramdhan , Tri Wahyudi (Al-Insyiroh: Jurnal Studi Keislaman, 2018)
This article tries to explain the basic understanding of the term 'lslam Nusantara', including its history and methodology. Since its inception, lslam Nusantara has become a heated discussion in the public discourse. Controversies and misunderstandings have occurred with those who support and against it. ln the circle of NU (Nahdhatul Ulama), there is a group who prefer the term lslam rahmatan lil 'alamiin than lslam Nusantara. This article aims to minimize the negative accusation against the concept of lslam Nusantara like the following phrases; lslam Nusantara has the potency to gnaw the principle teachings of lslam, or lslam Nusantara has deviated from the teaching of Ahlus Sunnah Waljama'ah (Aswaia). The conclusion from this study is the dialectics between religions that have moral and universal values with the culture and traditions of the people of Indonesia to form a distinctive style of Indonesian Islam is commonly called Islam Nusantara. Islam Nusantara is legitimate from the standpoint of epistemological